(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Swallowing are complex behaviours in which food passes from the mouth to stomach and during swallow airway protection happens minimizing food entering into lungs. In acute stage of stroke, dysphagia is found in up to 76% of patients and an increased mortality rate following aspiration is observed (Daniels & Brailey, 2009).Method: The main objectives of the study were to identify specific signs and symptoms specific to type and site of brain infarcts with stroke. This is a prospective study done in an acute hospital. This study has a sample size of 222 patients, with age range 20 - 75 years. The methodology included direct bedside swallow assessment, use of The Mann Assessment of Swallowing Ability (MASA) and kinematic analysis of Video fluoroscopic Evaluation of Swallowing.Results: The study showed that 55.9% of patients belonged to 51 to 70 years followed by 25.2% of patients belonging to 31-50 years.76.5% of patients had hemorrhagic stroke and 12.1% had ischemic strokes. On analyzing the symptoms exhibited by 222 patients following stroke 94.5% were dysarthria/slurred speech, 39.1% had aphasia, 58.1% had Right sided facial weakness, 26.5% had Left sided facial weakness. On administering Mann Assessment of Swallowing Ability (MASA) 31.9% of study patients had no dysphagia. 25.2% of patients had Mild dysphagia with mild aspiration risk. 2.2% of patients had Moderate dysphagia with mild aspiration risk.PAS score parameters were significantly (0.040) associated MASA score parameters. The VFSS parameters mainly tongue control (p=0.044; phi=0.494), laryngeal closure (p=0.050; phi=0.424), Initiation of Pharyngeal Swallow (p=0.095; phi=0.296), laryngeal elevation (p=0.027; phi=0.197), Epigiottic Movement (p=0.093; phi=0.339), Tongue Bolus Retraction (p=0.045; phi=0.295), and pharyngeal residue (p=0.055; phi-0.239) were significantly associated with site of infarct in addition to mild intensity of association.